1981
DOI: 10.1111/j.1365-2133.1981.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular psoriasis

Abstract: This is a report on ten patients with follicular psoriasis. Two distinct clinical types could be distinguished. An adult form, seen especially in women, presented with widespread psoriasis in which follicular lesions occurred on both thighs as part of the efflorescence. Follicular lesions were aggregated to form isolated asymmetrical plaques on the trunks of children with inactive psoriasis. The histological findings in follicular psoriasis varied according to the age of the lesion. In the early lesion there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 3 publications
4
29
0
Order By: Relevance
“…Including our case, 13 of 24 (54.2%) patients reported in the literature were female (Table ). In the nine cases in which race was reported, seven (78%) patients were black and one was Asian . Although previous reports have suggested that follicular psoriasis skews toward female and darker‐skinned patients, our review of the literature does not support this.…”
Section: Discussionmentioning
confidence: 99%
“…Including our case, 13 of 24 (54.2%) patients reported in the literature were female (Table ). In the nine cases in which race was reported, seven (78%) patients were black and one was Asian . Although previous reports have suggested that follicular psoriasis skews toward female and darker‐skinned patients, our review of the literature does not support this.…”
Section: Discussionmentioning
confidence: 99%
“…The exact incidence is unknown, as we found only three reports mentioning a total of 15 cases in the literature. [478] It affects both the sexes and although two thirds of these occurred in adults, cases have been described in children under the age of 10 years. [7] Lesions follow a chronic course ranging from 6 months to 23 months.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Two clinical subtypes have been described. [7] The adult form is more common in females, presenting with discrete hyperkeratotic papules usually involving the thighs. [7] The rarer childhood form presents either as grouped, asymmetrical, horny, follicular lesions affecting the trunk, axillae, and bony prominences or as a wide-spread eruption resembling pityriasis rubra pilaris,[78] except that the latter has typical islands of spared skin associated with an orange-red erythema and palmoplantar keratoderma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations